2011
DOI: 10.1017/s0266467411000150
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical legitimate pollination in distylous Palicourea demissa (Rubiaceae): the role of nectar production and pollinator visitation

Abstract: Abstract:We investigated morph differences in attributes that contribute to rewarding floral visitors of the distylous shrub Palicourea demissa at La Mucuy cloud forest in Venezuela. In both morphs, we measured nectar production from flowers subjected to repeated removals at 2-h intervals (10 plants per morph) and flowers that accumulated nectar for 24 h (10 plants per morph). In both cases, floral visitors were excluded. In addition, we quantified nectar availability (30 plants per morph), floral visitation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
2
15
0
1
Order By: Relevance
“…barbifl ora, Teixeira y Machado 2004a, b;Palicourea demissa, Valois-Cuesta et al, 2011), aunque otros estudios han mostrado diferencias (Palicourea padifolia, Ornelas et al, 2004, Fagopirum esculentum, Cawoy et al, 2008. Una oferta de néctar diferencial entre los morfos fl orales quizás podría generar tasas diferenciales de visita y de deposición de polen (Valois-Cuesta et al, 2011), y eventualmente, ello podría acarrear consecuencias negativas sobre el éxito reproductivo de las plantas (Manetas y Petropoulou, 2000). En nuestro estudio, las plantas de ambos morfos y sometidas a tratamientos de remoción fueron polinizadas artifi cialmente, sin evaluar los patrones de visita por polinizadores; por ello nuestros resultados sólo pueden ser conclusivos con respecto a la compensación diferencial de néctar entre morfos.…”
Section: Discussionunclassified
“…barbifl ora, Teixeira y Machado 2004a, b;Palicourea demissa, Valois-Cuesta et al, 2011), aunque otros estudios han mostrado diferencias (Palicourea padifolia, Ornelas et al, 2004, Fagopirum esculentum, Cawoy et al, 2008. Una oferta de néctar diferencial entre los morfos fl orales quizás podría generar tasas diferenciales de visita y de deposición de polen (Valois-Cuesta et al, 2011), y eventualmente, ello podría acarrear consecuencias negativas sobre el éxito reproductivo de las plantas (Manetas y Petropoulou, 2000). En nuestro estudio, las plantas de ambos morfos y sometidas a tratamientos de remoción fueron polinizadas artifi cialmente, sin evaluar los patrones de visita por polinizadores; por ello nuestros resultados sólo pueden ser conclusivos con respecto a la compensación diferencial de néctar entre morfos.…”
Section: Discussionunclassified
“…; Massinga, Johnson & Harder ; Hernández & Ornelas ; Brys et al . ; Wolfe, Massinga & Johnson ; Valois‐Cuesta, Soriano & Ornelas ). Pollen movement between vs. within morphs has also been investigated under natural conditions by either using pollen fluorescent dyes (Baena‐Díaz et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Ornelas et al . ; Massinga, Johnson & Harder ; Hernández & Ornelas ; Brys & Jacquemyn ; Valois‐Cuesta, Soriano & Ornelas ). The proportion of incompatible pollen may range from as much as 99·3% on stigmas of L‐flowers, as in Lithospermum caroliniense (Levin ), to as little as 7·7% on stigmas of S‐flowers, as in Pentanisia prunelloides (Massinga, Johnson & Harder ), and may depend on corolla length and form (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that in different distylous plant species some characteristics of the floral morphs related to the attractiveness towards the pollinators, such as the floral display and reward production, are not equal (e.g., Contreras & Ornelas 1999, Barrett 1990, Faivre 2000, Salinas-Esquivel et al 2013, Valois-Cuesta et al 2011. Likewise, it has been suggested that these differences could promote an asymmetrical pollen flow between floral morphs due to a differential attraction of pollinators (Valois-Cuesta et al 2011. In addition, the attraction of the antagonists species can also be different between morphs (Ornelas et al 2004b, Irwin & Adler 2006.…”
Section: Discussionmentioning
confidence: 99%